Socio-economic implications of forest-based biofuels for marine transportation in the Arctic: Sweden as a case study - Yacout, Dalia M. M.; Tysklind, Mats; Upadhyayula, Venkata K. K. (Frontiers in Climate, 2024)
Arctic melting is an effect of climate change; the use of fossil fuels in marine shipping emits large amounts of air emissions that impact climate change, and Arctic aquatic and human life. Swedish pulp and paper mills generate large amounts of waste and side streams that could be utilized. The production of forest-based biofuel may be a promising solution to achieve sustainable Arctic marine shipping. This review highlights the socio-economic impacts associated with the production of forest-based biofuel in Sweden, the related opportunities, challenges, knowledge gaps, and further need of research.From the economic perspective, it was found that the production and use of forest-based biofuel have short and long-term economic sustainability benefits: a) short-term benefits, the use of the waste and side streams of the pulp and paper industry is a low-cost available feedstock, unlike first-generation biofuel from crops like corn forest-based biofuels neither require additional land use, water resources nor compete with food. b) Long-term benefits: i) the Swedish shipping sector depends on imported fossil fuels, these new biofuels can replace partly those imported fossil fuels that will reduce shipping costs, and generate economic benefits for local consumers. ii) Usage of forest-based biofuels as blends with conventional fuels in existing engines will reduce greenhouse gas emissions from the Arctic shipping to the set limits in the region. iii) One of the important socio-economic impacts of forestbased biofuel production and use is the new job creation and employment opportunities that will impact the local communities and livelihoods of indigenous people in the area. From a societal perspective, stakeholder involvement is essential to address the sustainability challenges of biofuel production: EU policymakers need to encourage the production and use of biofuels by developing policies that promote biofuel use. Further studies are needed to develop more efficient and low-cost biofuel production routes, more investments in related research and development are required as well. Local indigenous communities must be involved in the decision-making process through surveys, local dialogues, and research studies. The production of forest-based biofuels has great potential and many social-economic impacts alongside the environmental benefits.